Protocol for a systematic review and meta-analysis of the impact of cervical cancer prevention initiatives in Ghana - Emmanuel Timmy Donkoh; Iddrisu Wahab Abdul; Abraham Kwadzo Ahiakpa; Isaac Williams; Rita Nyaaba Akologo; Stephen Danyo; Chrysantus Kubio; Kofi Effah; Joseph Emmanuel Amuah (PLoS ONE, 2025)
Background Cervical cancer, though preventable, remains the second most diagnosed cancer and the primary cause of cancer-related deaths among females in Sub-Saharan Africa. The significance of coordinated screening programmes for reducing the burden of cervical cancer in Africa is not well documented. This systematic review will summarize published reports from key databases, grey literature and programme reports to assess the performance of cervical cancer prevention programmes in Ghana. Methods To be eligible for inclusion, interventions must target Ghanaian women with cervical cancer screening and prevention strategies using methods such as visual inspection with acetic acid (VIA), mobile colposcopy, HPV DNA testing, cytology (Pap smear), and treatment approaches such as cryotherapy, thermal ablation, loop electrosurgical excision procedure (LEEP). A comprehensive electronic search strategy will be used to identify studies published since database inception, and indexed in MEDLINE, EMBASE, CINAHL and Web of Science. The search strategy will include MeSH terms (and synonyms) relevant to cervical cancer, screening/treatment methods, geographic focus and implementing institution. We will include searches for grey literature, recognizing the value of programmatic and governmental reports that might not appear in traditional databases. Search results will be summarized in line with PRISMA guidelines. The GRADE (Grading of Recommendations Assessment, Development and Evaluation) approach will be used to evaluate and document evidence certainty for all outcomes, internal validity of included reports, inconsistency, indirectness, imprecision, and publication bias. Where sufficient homogeneity exists among included studies in terms of interventions, study designs, populations, and outcome measures, we will perform a meta-analysis to calculate pooled effect estimates and their corresponding 95% confidence intervals. Significance This systematic review will assess the performance and impact of cervical cancer screening and prevention programmes conducted in Ghana to date and identify what contextual strategies have delivered the most impact as well as highlight what gaps remain in our understanding of how a nationwide screening programme can be properly construed for maximum impact.